PENGGALAN PASANGAN PERCAKAPAN DALAM DIALOG MATA NAJWA: Pura-pura Penjara-Sel Mewah Lutfi Hasan Ishak (Kajian Analisis Wacana) - Yusrina Yusrina; Haerul Haerul; Lilis Suryani; Sasmayunita Sasmayunita (Humano: Jurnal Penelitian, 2023)
This study aims to describe the form of the conversation partner fragments in the Mata Najwa dialogue on Najwa Shihab's YouTube channel. This type of research is a qualitative research. The method used is descriptive method. The object under study is a video conversation between Najwa Shihab and Lufti Hasan Ishak on Najwa Shihab's YouTube channel entitled Mata najwa Part1: Pretending to be a Prison – Lutfi Hasan Ishaq's Luxury Cell. The results of the study show that the forms of conversational fragments in the dialogs of Najwa Shihab and Lutfi Hasan Ishaq include: 1) fragments of commemorations; 2) The fragment asks for an explanation; 3) Greetings and greetings/greetings; 4) Fragments of Application and Approval; and 5) Fragments of accusations and denial. The most dominant part of the conversation pair in the Mata Najwa dialogue is the part of asking for an explanation and the part of greeting and greeting. Based on the theory put forward by Richard (in Syamsuddin, 2012) no fragments of conversation pairs were found: 1) fragments of calls and answers; 2) fragment of service offer; 3) fragment of offer and refusal.